2015
DOI: 10.1177/0300985815591080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Porcine Epidemic Diarrhea Virus Isolate US/Iowa/18984/2013 Infection in 1-Day-Old Cesarean-Derived Colostrum-Deprived Piglets

Abstract: Porcine epidemic diarrhea virus (PEDV) was first recognized in North America in April 2013 and has since caused devastating disease. The objective of this study was to characterize disease and viral detection associated with an original North American PEDV isolate inoculated in neonatal piglets. Thirty-six 1-day-old cesarean-derived and colostrum-deprived piglets were randomly assigned to the control (n ¼ 16) or challenged group (n ¼ 20); the latter were orogastrically inoculated with 1 ml of US/Iowa/ 18984/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 19 publications
10
60
0
Order By: Relevance
“…Previous studies showed that viraemia can occur in the acute stage of infection with US PEDV prototype isolates (Jung et al, 2014;Madson et al, 2016). In the present study, we also detected PEDV RNA in serum samples.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies showed that viraemia can occur in the acute stage of infection with US PEDV prototype isolates (Jung et al, 2014;Madson et al, 2016). In the present study, we also detected PEDV RNA in serum samples.…”
Section: Discussionsupporting
confidence: 74%
“…In the current study, high levels of PEDV RNA were detected in small intestine, caecum, colon and mesenteric lymph nodes, while low levels of PEDV RNA were detected in non-enteric tissues (tonsil, heart, lung, liver, spleen, kidney and muscle) from pigs inoculated with either prototype or S-INDEL-variant PEDV. Previous studies indicated that PEDV viral antigen (US prototype isolates) could be detected in small intestine, mesenteric lymph node, and some colon and spleen tissues (Jung et al, 2014(Jung et al, , 2015bMadson et al, 2016), but other non-enteric tissues such as lung, heart, kidney and liver were all negative for PEDV antigen (Madson et al, 2016). Therefore, detection of PEDV RNA does not necessarily mean that PEDV replicates in all of these non-enteric tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental PEDV infections in seronegative suckling pigs, during the incubation period, i.e. at approximately PIH 12-24, PEDV antigen-positive cells were seen throughout the small intestine and as many as 30-100% of the absorptive epithelial cells were positive (Debouck et al, 1981;Madson et al, 2015), consistent with fecal virus shedding in subclinical pigs. After that, during the clinical period, moderate to large numbers of PEDV antigen-positive cells were observed throughout the small intestine (Debouck et al, 1981;Jung et al, 2015a;Madson et al, 2015).…”
Section: Intestinal Replication Of Pdcov During Disease Progressionmentioning
confidence: 74%
“…Additionally, a portion of the jejunum and ileum were fixed in 10% neutral buffered formalin for histopathology. The villous atrophy is a typical histopathological change of the infection of a highly virulent PEDV44454647. And the villous height and crypt depth (VH:CD) ratios would be calculated using a computerized image system with as previous described44.…”
Section: Methodsmentioning
confidence: 99%